2015
DOI: 10.1186/s12889-015-2628-y
|View full text |Cite
|
Sign up to set email alerts
|

Stories for change: development of a diabetes digital storytelling intervention for refugees and immigrants to minnesota using qualitative methods

Abstract: BackgroundImmigrants and refugees are affected by diabetes-related health disparities, with higher rates of incident diabetes and sub-optimal diabetes outcomes. Digital storytelling interventions for chronic diseases, such as diabetes may be especially powerful among immigrants because often limited English proficiency minimizes access to and affects the applicability of the existing health education opportunities. Community-based participatory research (CBPR), whereby community members and academia partner in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 27 publications
0
106
0
Order By: Relevance
“…CBPR-based strategies that have been successfully employed to recruit such groups include engaging lay community members to recruit participants, developing recruitment plans informed by local community advisory groups, recruiting via locally-relevant channels (e.g., radio, community-based venues), partnering with trusted local organizations and leaders to promote recruitment, and otherwise leveraging local social networks (Bryant et al, 2014; Greiner et al, 2014; Kreuter et al, 2012). Although the majority of published CBPR studies have been conducted with racial/ethnic minority and low-SES populations, emerging literature indicates CBPR methods can be similarly effective in recruiting participants from other underrepresented/marginalized groups such as sexual minority populations (Bryant et al, 2014; Rhodes et al, 2014), persons with disabilities (Nicolaidis et al, 2013), immigrants and refugees (Njeru et al, 2015), and individuals experiencing homelessness and co-occurring mental illness (Henwood et al, 2013). In a notable example underscoring the potential role of CBPR to foster inclusion, an evidential review of CBPR and smoking cessation interventions in marginalized communities found that studies with relatively low community involvement generally had challenges with participant recruitment (Andrews et al, 2012).…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…CBPR-based strategies that have been successfully employed to recruit such groups include engaging lay community members to recruit participants, developing recruitment plans informed by local community advisory groups, recruiting via locally-relevant channels (e.g., radio, community-based venues), partnering with trusted local organizations and leaders to promote recruitment, and otherwise leveraging local social networks (Bryant et al, 2014; Greiner et al, 2014; Kreuter et al, 2012). Although the majority of published CBPR studies have been conducted with racial/ethnic minority and low-SES populations, emerging literature indicates CBPR methods can be similarly effective in recruiting participants from other underrepresented/marginalized groups such as sexual minority populations (Bryant et al, 2014; Rhodes et al, 2014), persons with disabilities (Nicolaidis et al, 2013), immigrants and refugees (Njeru et al, 2015), and individuals experiencing homelessness and co-occurring mental illness (Henwood et al, 2013). In a notable example underscoring the potential role of CBPR to foster inclusion, an evidential review of CBPR and smoking cessation interventions in marginalized communities found that studies with relatively low community involvement generally had challenges with participant recruitment (Andrews et al, 2012).…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…The literature, however, primarily focuses on the benefits of the story narrative-as-message on audiences, rather than the benefits of the creative storytelling process itself on workshop participants as a health intervention. A range of approaches may be subsumed under the heading of "digital storytelling," ranging from those that are distinctly participant driven (Njeru et al, 2015;Williams et al, 2015), to those that are less collaborative in nature and center more on the use of stories elicited from, but not produced by, 649353Q HRXXX10.1177/1049732316649353Qualitative Health ResearchGubrium et al…”
Section: Introductionmentioning
confidence: 98%
“…Gubrium & Turner, 2011). Studies conducted in this area are typically participatory where participants make a digital story in a group process (Cunsolo Willox, Harper, Edge, 'My Word': Storytelling Digital Media Lab, & Rigolet Inuit Community Government, 2013;Ferrari, Rice, & McKenzie, 2015;LeMarre & Rice, 2016;Njeru et al, 2015;Rice, Chandler, Harrison, Liddiard, & Ferrari, 2015) or nonparticipatory, where participants watch a digital story created by others (Christiansen, 2011;Eggenberger & Sandars, 2016;Levett-Jones, Bowen, & Morris, 2015).…”
Section: Digital Storytelling As Art-based Methodsologymentioning
confidence: 99%
“…Digital storytelling has been used as a culturally appropriate participatory research methodology with indigenous people because it supports communities to cocreate data with researchers using traditional storytelling methods (Cueva et al, 2016;Cunsolo Willox et al, 2013;Njeru et al, 2015). Making digital stories with indigenous communities is described as a transformative process because people work and learn together, and share and discuss perspectives and experiences to produce knowledge that has relevance for the local community, researchers, policy makers, government, and international audiences (Cunsolo Willox et al, 2013).…”
Section: Digital Storytelling As Art-based Methodsologymentioning
confidence: 99%
See 1 more Smart Citation